Method for synthesizing perovskite gain medium by using diaminodiphenyl sulfone as ligand

By using diaminodiphenylsulfone as a ligand to synthesize perovskite gain medium, the problem of insufficient high-gloss gain threshold and stability in 3D perovskite materials in lasers is solved, lower gain threshold and higher stability are achieved, and the performance and reliability of the laser are improved.

CN119662237APending Publication Date: 2025-03-21YANGTZE DELTA REGION INST (QUZHOU) UNIV OF ELECTRONIC SCI & TECH OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411765310.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

3D organic-inorganic perovskite materials have problems with insufficient high-light gain threshold and stability in laser applications, especially in the face of high-power continuous excitation of nanosecond lasers.

Method used

Diaminodiphenylsulfone is used as a ligand to synthesize perovskite gain medium through surface engineering to lower the light gain threshold and improve the light, heat and moisture stability of the material.

Benefits of technology

The laser gain threshold of the perovskite gain medium is significantly reduced, the long-term optical gain stability of the material is improved, and the efficiency and service life of the laser are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662237A_ABST
    Figure CN119662237A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lasers, and discloses a method for synthesizing a perovskite gain medium by taking diaminodiphenyl sulfone as a ligand, and an optical gain threshold value of a perovskite gain film synthesized based on the diaminodiphenyl sulfone ligand is reduced to 34.6% of the original optical gain threshold value under the action of nanosecond laser pumping. After continuous pumping of nanosecond laser, the optical gain intensity is only reduced to 90% of the original optical gain intensity 24 hours later. The optical gain intensity of a sample which is not optimized by diaminodiphenyl sulfone is rapidly reduced under the continuous pumping action of nanosecond laser. According to the method for synthesizing the perovskite gain medium by using the diaminodiphenyl sulfone as the ligand, the technical problems of high light threshold and insufficient light stability of a laser gain medium are solved, and a foundation is laid for the development of a perovskite laser.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lasers, and in particular to a method for synthesizing a perovskite gain medium by taking diaminodiphenyl sulfone as a ligand. Background Art

[0002] Organic-inorganic hybrid perovskite is an excellent laser gain material. Due to its excellent optoelectronic properties, such as high light absorption coefficient, wide spectral absorption, long carrier diffusion length, low non-radiative recombination rate and adjustable band gap, organic-inorganic hybrid perovskite materials have shown great potential in optoelectronic fields such as photovoltaics, light-emitting diodes and lasers in recent years. However, in laser applications, the high optical gain threshold and insufficient stability of perovskite materials limit their practical application in high-efficiency lasers. These two problems have been widely reported in multiple studies and published patents.

[0003] First, the optical gain threshold of organic-inorganic hybrid perovskite materials is high. Due to the presence of defect states and grain boundaries in perovskite materials, higher pump energy is often required to achieve laser emission, which greatly limits the practical application of perovskite lasers, especially in low-energy and miniaturized devices. The literature (Nano Letters 18,3221,2018) points out that quasi-two-dimensional organic-inorganic hybrid perovskite crystals overcome the shortcomings of grain boundaries and use the quantum well effect of the quasi-two-dimensional structure to achieve the effect of reducing the optical gain threshold. However, this method does not work for 3D organic-inorganic hybrid perovskites, and growing crystals will increase costs and cycles.

[0004] Secondly, the optical gain stability of 3D perovskite materials is poor, and they are prone to photodegradation under long-term light irradiation. Under continuous laser irradiation, the crystal structure of perovskite materials is prone to degradation, resulting in a decrease in the performance of the gain medium. This problem is related to the intrinsic defects of the material and improper treatment of the surface and interface. These degradations can lead to a significant attenuation of the optical gain, affecting the long-term stability of the device. The literature (Nature, 2019, 567, 511-515) proposes that by passivating the perovskite film with large organic cations, the defect density can be effectively reduced and the optical stability of the material can be improved. However, although these methods have improved the optical gain characteristics of perovskite materials to a certain extent, they still fail to fully solve the problems of excessively high optical gain thresholds and insufficient stability, especially in the face of high-power continuous excitation of nanosecond lasers.

[0005] At present, researchers have also achieved a reduction in the gain threshold of perovskite materials through regulation of preparation methods. For example, the public patent (CN118440109A) proposes a method for synthesizing low-threshold perovskite laser materials using piperonylamine as a ligand, which greatly reduces the optical gain threshold of quasi-two-dimensional perovskites. However, this method is only effective for quasi-two-dimensional materials, and no effective method has been reported to regulate 3D perovskite films with a wider range of applications. At the same time, this method is limited to laser operations using femtosecond lasers as pump sources.

[0006] Therefore, how to effectively lower the optical gain threshold of 3D organic-inorganic perovskite materials and improve the long-term stability of their optical gain, especially when facing nanosecond laser pumping with higher thermal effects, is still a technical problem that needs to be solved urgently in the field of perovskite lasers.

[0007] To this end, the present invention proposes a method for synthesizing a perovskite gain medium using diaminodiphenyl sulfone as a ligand. This method is based on surface engineering techniques to further reduce the optical gain threshold and improve the stability of the optical gain, providing a solid technical foundation for the efficient and long-term use of 3D organic-inorganic hybrid perovskite laser devices. Summary of the invention

[0008] In order to solve the technical problems that the current organic-inorganic perovskite has a relatively high optical gain threshold, insufficient photostability, and is very easy to be distorted under the action of optical pumping, the present invention proposes a method for synthesizing a perovskite gain medium using diaminodiphenyl sulfone as a ligand, aiming to achieve a reduction in the optical gain threshold and an improvement in stability.

[0009] The method for synthesizing a perovskite gain medium using diaminodiphenyl sulfone as a ligand proposed by the present invention comprises the following steps:

[0010] S1. Place the substrate in acetone, deionized water, isopropanol, and ethylene glycol in turn and ultrasonicate for 10-15 minutes each, then blow dry with nitrogen for later use;

[0011] S2, Precision MX, FX and PbX 2 Dissolve in a solvent according to a certain proportion, stir thoroughly to obtain a first solution; accurately weigh diaminodiphenyl sulfone and dissolve in a solvent, stir thoroughly to obtain a second solution;

[0012] S3, mixing the first solution and the second solution in a volume ratio of 1:1, stirring for 1-8 hours after mixing, to obtain a precursor solution;

[0013] S4, performing hydrophilic treatment on the substrate obtained in step S1;

[0014] S5, taking an appropriate amount of precursor solution and dropping it on the rotating substrate, i.e. spin coating;

[0015] S6, transferring the perovskite obtained in step S5 to a hot stage for annealing;

[0016] Wherein, X is a mixture of one or more halogen anions; MX is one or two of formamidine hydrohalide and methylamine halide; FX is one or more of cesium halide, rubidium halide, n-butylammonium halide, benzylamine halide, n-octylamine hydrohalide, isobutylammonium halide, phenylpropylamine halide, aminovaleric acid halide, 1-naphthylmethylammonium halide, guanidine hydrohalide, n-butylamine halide, phenylbutylamine halide, ethylamine hydrohalide and phenethylamine halide.

[0017] Preferably, the solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, γ-butyrolactone and N-methylpyrrolidone.

[0018] Preferably, the substrate includes but is not limited to a silicon wafer, a silicon wafer containing an oxide layer, a high-purity quartz wafer, a mica wafer, and a sapphire.

[0019] Preferably, the spin coating speed is 3000-6000 rpm, and the spin coating time is 20-60s.

[0020] Preferably, the annealing temperature is 80-120° C., and the annealing time is 10-30 min.

[0021] Preferably, the concentration of the Pb ions is 0.2-0.4 mol / L.

[0022] Preferably, the concentration of the diaminodiphenyl sulfone is 0.5-80 mg / ml.

[0023] Compared with the related art, the method for synthesizing the perovskite gain medium using diaminodiphenyl sulfone as a ligand proposed in the present invention has the following beneficial effects:

[0024] 1. Significantly reduce the gain threshold: This patent uses diaminodiphenyl sulfone (DDS) as a surface modification ligand for perovskite materials, which effectively passivates surface defects and reduces non-radiative recombination, thereby significantly reducing the laser gain threshold of the perovskite gain medium. This performance improvement is comparable to traditional inorganic ligands (such as PbI 2 、ZnBr 2 ) or organic small molecule ligands (such as PMA, PMAI) modified perovskite materials are more significant, effectively improving the efficiency of the laser.

[0025] 2. Enhance material stability: The diaminodiphenyl sulfone ligand binds to the Pb on the surface of the perovskite 2+It forms stable chemical bonds with halogen ions, significantly improving the light, heat and moisture stability of perovskite materials. Compared with the method of using ordinary organic amine or alkyl ligand modification, the DDS ligand in this patent can provide better environmental stability and effectively extend the service life of perovskite materials in practical applications.

[0026] 3. Controllable preparation process: This patent provides a simple, efficient and controllable perovskite material preparation process. The stability of the DDS ligand in the solution and its good compatibility with the perovskite precursor improve the growth uniformity and repeatability of the perovskite film. Compared with traditional methods, this patented method does not require high temperature or complex post-processing processes, reducing production costs and equipment requirements.

[0027] 4. Wide applicability: Due to the excellent chemical stability and strong coordination ability of diaminodiphenyl sulfone ligand, this method is not only applicable to conventional three-dimensional perovskite materials (such as MAPbI 3 , FAPbBr 3 ), and is also applicable to two-dimensional layered perovskites and hybrid perovskite materials (such as Ruddlesden-Popper type perovskites). This advantage makes this patent have a wide range of application prospects and can meet the needs of different optoelectronic devices, including lasers, LEDs and photovoltaic cells.

[0028] 5. Environmental friendliness: Compared with some traditional passivators (such as toxic heavy metal compounds or surfactants with high fluorine content), diaminodiphenyl sulfone is a low-toxic, environmentally friendly ligand that complies with the principles of green chemistry. While ensuring material performance, it reduces potential harm to the environment and human health. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The spectrum changes of Example 1 of the present invention and Comparative Example 1 under nanosecond laser pumping;

[0030] Figure 2 The curves showing the change of the integrated luminous intensity with the pump power of Example 1 and Comparative Example 1 of the present invention;

[0031] Figure 3 The stability test curves of Example 1 of the present invention and Comparative Example 1 under nanosecond laser pumping. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with the accompanying drawings and implementation modes.

[0033] The present invention provides a method for synthesizing a perovskite gain medium using diaminodiphenyl sulfone as a ligand, comprising the following steps:

[0034] Step 1: Place the substrate in acetone, deionized water, isopropanol, and ethylene glycol in turn and ultrasonicate for 10-15 minutes each, then blow dry with nitrogen for later use;

[0035] Step 2: Precise MX, FX and PbX 2 Dissolve in a solvent according to a certain proportion, stir thoroughly to obtain a first solution; accurately weigh diaminodiphenyl sulfone and dissolve in a solvent, stir thoroughly to obtain a second solution;

[0036] Step 3, mixing the first solution and the second solution in a volume ratio of 1:1, stirring for 1-8 hours after mixing, to obtain a precursor solution;

[0037] Step 4, performing hydrophilic treatment on the substrate obtained in step 1;

[0038] Step 5: Take an appropriate amount of precursor solution and drop it on the rotating substrate, i.e. spin coating;

[0039] Step 6, transferring the perovskite obtained in step 5 to a hot stage for annealing;

[0040] Wherein, X is a mixture of one or more halogen anions; MX is one or two of formamidine hydrohalide and methylamine halide; FX is one or more of cesium halide, rubidium halide, n-butylammonium halide, benzylamine halide, n-octylamine hydrohalide, isobutylammonium halide, phenylpropylamine halide, aminovaleric acid halide, 1-naphthylmethylammonium halide, guanidine hydrohalide, n-butylamine halide, phenylbutylamine halide, ethylamine hydrohalide and phenethylamine halide.

[0041] In the above scheme, the solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, γ-butyrolactone and N-methylpyrrolidone.

[0042] In the above scheme, the substrate includes but is not limited to a silicon wafer, a silicon wafer containing an oxide layer, a high-purity quartz wafer, a mica wafer, and a sapphire.

[0043] In the above scheme, the spin coating speed is 3000-6000 rpm, and the spin coating time is 20-60s.

[0044] In the above scheme, the annealing temperature is 80-120° C., and the annealing time is 10-30 min.

[0045] In the above scheme, the concentration of the Pb ions is 0.2-0.4 mol / L.

[0046] In the above scheme, the concentration of diaminodiphenyl sulfone is 0.5-20 mg / ml.

[0047] Comparative Example 1

[0048] (1) In a glove box, 0.175 mmol of rubidium chloride (RbCl), 0.35 mmol of cesium iodide, 0.883 mmol of formamidine hydroiodic acid (FAI), and 3.15 mmol of lead iodide (PbI 2 ), 0.175 mmol was dissolved in 10 ml of a mixed solution of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF), wherein the volume ratio of DMSO to DMF was 1:3.

[0049] (2) Stirring at room temperature for 6 hours at a stirring speed of 3000 rpm. Then filtering the solution with a 0.3 μm organic filter to obtain a precursor solution I.

[0050] (3) A 10 mm*10 mm*6 mm high-purity quartz sheet was used as the substrate, and ultrasonically cleaned in deionized water, acetone, and isopropanol for 5 minutes in sequence, and then dried with nitrogen.

[0051] (4) The quartz plate obtained in step (3) is treated with plasma for 10 minutes to obtain a highly hydrophilic quartz plate.

[0052] (5) Take 50 μL of the precursor solution and drop it onto a high-speed rotating quartz plate at a speed of 5000 rpm and a spin coating time of 40 s.

[0053] (6) The quartz plate was transferred to a heating platform and baked at 90°C for 30 min. 0.05 Cs 0.1 FA 0.9 PbI 2.8 Cl 0.2 Perovskite gain films.

[0054] Example 1

[0055] (1) In a glove box, 0.175 mmol of rubidium chloride (RbCl), 0.35 mmol of cesium iodide, 0.883 mmol of formamidine hydroiodic acid (FAI), and 3.15 mmol of lead iodide (PbI 2 ), 0.175 mmol was dissolved in 10 ml of a mixed solution of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF), wherein the volume ratio of DMSO to DMF was 1:3, to obtain a first solution.

[0056] (2) Weigh 50 mg of diaminodiphenyl sulfone, dissolve it in 5 ml of DMSO solution, and continue stirring for 6 h until it is completely dissolved to obtain a second solution.

[0057] (3) Take 3 ml of the first solution and the second solution respectively, mix them, and stir them at room temperature for 6 hours at a stirring speed of 3000 rpm. Then filter the solution with a 0.3 μm organic filter to obtain a precursor solution II.

[0058] (4) A 10 mm*10 mm*6 mm high-purity quartz sheet was used as the substrate, and ultrasonically cleaned in deionized water, acetone, and isopropanol for 5 minutes in sequence, and then dried with nitrogen.

[0059] (5) The quartz plate obtained in step (3) is treated with plasma for 10 minutes to obtain a highly hydrophilic quartz plate.

[0060] (6) Take 50 μL of the precursor solution and drop it onto a high-speed rotating quartz plate at a speed of 5000 rpm and a spin coating time of 40 s.

[0061] (7) The quartz plate was transferred to a heating table and baked at 90°C for 30 min. The Rb optimized with diaminodiphenyl sulfone was obtained using precursor solution II. 0.05 Cs 0.1 FA 0.9 PbI 2.8 Cl 0.2 Perovskite gain films.

[0062] Example 2

[0063] The precursor solution was prepared by methods S1 and S2:

[0064] Method S1:

[0065] S1-1: In a glove box, 5 mmol of lead bromide (PbBr 2 ), 4 mmol of formamidine hydrobromide (FABr) and 2 mmol of 1-naphthylmethylammonium bromide (NMABr) were dissolved in 10 ml of N,N-dimethylformamide (DMF).

[0066] S1-2: Stirring at room temperature for 12 hours at a stirring speed of 2500 rpm. Then, the solution was filtered using a 0.25 μm organic filter to obtain a quasi-two-dimensional organic-inorganic hybrid perovskite precursor solution III.

[0067] Method S2:

[0068] S2-1: In a glove box, 5 mmol of lead bromide (PbBr 2 ), 4 mmol of formamidine hydrobromide (FABr), and 2 mmol of 1-naphthylmethylammonium bromide (NMABr) were dissolved in 10 ml of N,N-dimethylformamide (DMF) to obtain a first solution.

[0069] S2-2: Weigh 50 mg of diaminodiphenyl sulfone, dissolve it in 5 ml of DMSO solution, and continue stirring for 6 hours until it is completely dissolved to obtain a second solution.

[0070] S2-3: Take 3 ml of the first solution and the second solution respectively, mix them, and stir them at room temperature for 12 hours at a stirring speed of 2500 rpm. Then filter the solution with a 0.25 μm organic filter to obtain a quasi-two-dimensional organic-inorganic hybrid perovskite precursor solution IV.

[0071] S2-4: Take a 10 mm*10 mm*6 mm high-purity quartz sheet as the substrate, ultrasonically clean it in deionized water, acetone, and isopropanol for 5 minutes in sequence, and blow dry it with nitrogen.

[0072] S2-5: The quartz plate obtained in step S2-4 is treated with plasma for 10 minutes to obtain a highly hydrophilic quartz plate.

[0073] S2-6: Take 30 μL of the precursor solution and drip it onto a high-speed rotating quartz plate at a speed of 6000 rpm for 30 seconds. At 20 seconds, add the anti-solvent ethyl acetate.

[0074] S2-7: The quartz plate was transferred to a heating table and baked at 75°C for 30 min. A quasi-two-dimensional organic-inorganic perovskite gain film (standard film) was obtained using precursor solution III. A quasi-two-dimensional organic-inorganic perovskite gain film optimized with diaminodiphenyl sulfone was obtained using precursor solution IV.

[0075] Compared with femtosecond lasers, nanolasers have stronger thermal effects. Therefore, with nanolasers as pump sources, the optical gain threshold of perovskite gain films is higher, and even optical gain cannot be generated due to the accumulation of thermal effects. Figure 1 The spectrum of Example 1 and Comparative Example 1 of the present invention is pumped by a 475nm nanosecond laser. It can be seen from the figure that as the pump power density increases, the spectral intensity increases. When the pump power density is greater than a certain threshold, a peak gradually appears in the 810-820nm region. This shows that under nanosecond laser pumping, both Example 1 and Comparative Example 1 have amplified spontaneous emission.

[0076] Figure 2 It is a curve showing the change of the integrated luminescence intensity with the pump power. As can be seen from the figure, the light gain threshold of Example 1 is smaller than the threshold in the comparative example. The gain threshold of the perovskite film optimized with diaminodiphenyl sulfone as the ligand is only 34.6% of the latter.

[0077] Figure 3This is a time stability test of Example 1 and Comparative Example 1. As can be seen from the figure, the optical gain intensity of the perovskite film in Comparative Example 1 collapses rapidly under nanosecond laser pumping until it is reduced to 40% of the original value. In sharp contrast, the perovskite film optimized by diaminodiphenyl sulfone shows high stability under nanosecond laser action. After 24 hours of continuous action, the optical gain intensity in Example 1 only drops to 90% of the initial value, indicating that after diaminodiphenyl sulfone optimization, the perovskite film can withstand long-term nanosecond laser pumping and has good optical stability.

[0078] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for synthesizing a perovskite gain medium using diaminodiphenyl sulfone as a ligand, characterized in that: The following steps are involved: S1. Place the substrate in acetone, deionized water, isopropanol, and ethylene glycol in turn and ultrasonicate for 10-15 minutes each, then blow dry with nitrogen for later use; S2, accurate MX, FX and PbX2 are dissolved in a solvent in proportion and stirred thoroughly to obtain a first solution; accurately weigh diaminodiphenyl sulfone and dissolve it in a solvent, and stir thoroughly to obtain a second solution; S3, mixing the first solution and the second solution in a volume ratio of 1:1, stirring for 1-8 hours after mixing, to obtain a precursor solution; S4, performing hydrophilic treatment on the substrate obtained in step S1; S5, taking an appropriate amount of precursor solution and dropping it on the rotating substrate, i.e. spin coating; S6, transferring the perovskite obtained in step S5 to a hot stage for annealing; Wherein, X is a mixture of one or more halogen anions; MX is one or two of formamidine hydrohalide and methylamine halide; FX is one or more of cesium halide, rubidium halide, n-butylammonium halide, benzylamine halide, n-octylamine hydrohalide, isobutylammonium halide, phenylpropylamine halide, aminovaleric acid halide, 1-naphthylmethylammonium halide, guanidine hydrohalide, n-butylamine halide, phenylbutylamine halide, ethylamine hydrohalide and phenethylamine halide.

2. The method for synthesizing a perovskite gain medium using diaminodiphenyl sulfone as a ligand according to claim 1, characterized in that: The solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, γ-butyrolactone and N-methylpyrrolidone.

3. The method for synthesizing a perovskite gain medium using diaminodiphenyl sulfone as a ligand according to claim 1, characterized in that: The substrate includes but is not limited to a silicon wafer, a silicon wafer containing an oxide layer, a high-purity quartz wafer, a mica wafer, and a sapphire.

4. The method for synthesizing a perovskite gain medium using diaminodiphenyl sulfone as a ligand according to claim 1, characterized in that: The spin coating speed is 3000-6000 rpm, and the spin coating time is 20-60s.

5. The method for synthesizing a perovskite gain medium using diaminodiphenyl sulfone as a ligand according to claim 1, characterized in that: The annealing temperature is 80-120° C., and the annealing time is 10-30 min.

6. The method for synthesizing a perovskite gain medium using diaminodiphenyl sulfone as a ligand according to claim 1, characterized in that: The concentration of the Pb ions is 0.2-0.4 mol / L.

7. The method for synthesizing a perovskite gain medium using diaminodiphenyl sulfone as a ligand according to claim 1, characterized in that: The concentration of the diaminodiphenyl sulfone is 0.5-80 mg / ml.

8. Application of the low-threshold and highly stable perovskite laser material according to claims 1 to 7 in the laser field.

Citation Information

Patent Citations

  • Method for synthesizing low-threshold perovskite laser material by using piperonylamine as ligand

    CN118440109A

  • Binary passivated perovskite precursor composition, perovskite light absorption layer prepared from composition and perovskite solar cell prepared from composition

    CN117460381A